Deification, Ethics, and Hermeneutics - Brown, Derek (Lumen et Vita, 2017)
This paper challenges ontologizing readings of Athanasian deification by dialoging with Jacques Derrida’s essay, Rams: Uninterrupted Dialogue – Between Two Infinities, the Poem. For Derrida, every relationship is marked by the trace of death: we know that one of us will die before the other. From this, Derrida develops an account of relationship, and ultimately friendship, that rests on trust and promise, on fidelity: I trust that you will carry on our relationship after I am gone, and I promise to do the same for you. Insofar as our relationship is a trusting one, then, it turns out that death marks an "inaugural cut," wherein I am opened to the possibility of relationship, to the possibility of carrying. Death is necessary, and yet horrible. I argue that this reading of death as constitutive of relationship is crucial to understanding the role of Christ’s death in Athanasius’s account of deification. In short, Christ’s death—and the sacramental offering of his body that follows—allows deification to be thought relationally, and so ethically. That is, we participate in the Trinity when we carry the risen Christ in ourselves. At the same time, this carrying is only possible because Christ is carrying us. This account troubles the dominant ontological, “Alexandrian,” categorization of Athanasius in two ways: Most basically, it argues that Christ’s death is not marginal to Athanasius’s theory—this contrary to ontologist readings that place too heavy and lopsided a focus on the “Incarnation.” More pronouncedly, it rejects the notion that, for Athanasius, receiving salvation is a passive reception of Christ’s incorporation of humanity—of an event that could only be interpreted and “understood” after the fact. The theological register pertinent to Athanasian deification is not one of interpretation and ontology, but is one of carrying, hospitality, and relationship.